Potential impact of the validated Predicting Abusive Head Trauma (PredAHT) clinical prediction tool: A clinical vignette study. (December 2018) - Cowley, Laura E.; Farewell, Daniel M.; Kemp, Alison M.
Abstract: Background: The validated Predicting Abusive Head Trauma (PredAHT) tool estimates the probability of abusive head trauma (AHT) in children <3 years old with intracranial injury. Objective: To explore the impact of PredAHT on clinicians' AHT probability estimates and child protection (CP) actions, and assess inter-rater agreement between their estimates and between their CP actions, before and after PredAHT. Participants and Setting: Twenty-nine clinicians from different specialties, at teaching and community hospitals. Methods: Clinicians estimated the probability of AHT and indicated their CP actions in six clinical vignettes. One vignette described a child with AHT, another described a child with non-AHT, and four represented "gray" cases, where the diagnosis was uncertain. Clinicians calculated the PredAHT score, and reported whether this altered their estimate/actions. The 'think-aloud' method was used to capture the reasoning behind their responses. Analysis included linear modelling, linear mixed-effects modelling, chi-square tests, Fisher's exact tests, intraclass correlation, Gwet's AC1 coefficient and thematic analysis. Results: Overall, PredAHT significantly influenced clinicians' probability estimates in all vignettes ( p  < 0.001), although the impact on individual clinicians varied. However, the influence of PredAHT on clinicians' CP actions was limited; after using PredAHT, 9/29 clinicians changed their CP actions in only 11/174 instances. Clinicians' AHT probability estimates and CP actions varied somewhat both before and after PredAHT. Qualitative data suggested that PredAHT may increase clinicians' confidence in their decisions when considered alongside other associated clinical, historical and social factors. Conclusions: PredAHT significantly influenced clinicians' AHT probability estimates, but had minimal impact on their CP actions.